Atrial fibrillation dashboard evaluation using the think aloud protocol. Issue 3 (21st October 2020) - de Lusignan, Simon; Liyanage, Harshana; Sherlock, Julian; Ferreira, Filipa; Munro, Neil; Feher, Michael; Hobbs, Richard
Abstract : Background: Atrial fibrillation (AF) is a common cardiac arrhythmia which is a major risk factor for stroke, transient ischaemic attacks and increased mortality. Primary care management of AF can significantly reduce these risks. We carried out an evaluation to asses the usability of an AF dashboard developed to improve data quality and the quality of care. Method: We developed an online dashboard about the quality of AF management for general practices of the Oxford Royal College of General Practitioners Research and Surveillance Centre network. The dashboard displays (1) case ascertainment, (2) a calculation of stroke and haemorrhage risk to assess whether the benefits of anticogulants outweigh their risk, (3) prescriptions of different types of anticoagulant and (4) if prescribed anticoagulant is at the correct dose. We conducted the think aloud evaluation, involving 24 dashboard users to improve its usability. Results: Analysis of 24 transcripts received produced 120 individual feedback items (ie, verbalised tasks) that were mapped across five usability problem classes. We enhanced the dashboard based on evaluation feedback to encourage adoption by general practices participating in the sentinel network. Conclusions: The think aloud evaluation provided useful insights into important usability issues that require further development. Our enhanced AF dashboard was acceptable to clinicians and its impact on data quality and care should be assessed in a formal study.